Gorilla - Marshall, E. G., 1910-; Jampel, Barbara (WQED/Pittsburg : National Geographic Society, 1981)
Calls attention to the plight of the gorilla, which is on the verge of extintion. Profiles a zookeeper, a research scientist, and a husband and wife team working on the mountain gorilla project. Film footage demonstrates the animals' intelligence, humanlike qualities, and the effects of their exploitation by humans.
Keywords: Gorillas